TGFβ1: An Indicator for Tumor Immune Microenvironment of Colon Cancer From a Comprehensive Analysis of TCGA - Wang, Jinyan; Wang, Jinqiu; Gu, Quan; Yang, Yan; Ma, Yajun; Zhang, Quan’an (Frontiers in Genetics, 2021)
Background: Tumor microenvironment (TME) and tumor-infiltrating immune cells (TICs) greatly participated in the genesis and development of colon cancer (CC). However, there are few researches exploring the dynamic modulation of TME. Methods: We analyzed the proportion of immune/stromal component and TICs in TME of 473 CC samples and 41 normal samples from TCGA database through ESTIMATE and CIBERSORT algorithms. Correlation analysis was conducted to evaluate the association between immune/stromal component in TME and clinicopathological characteristics of CC patients. The difference analysis was performed to obtain the differentially expressed genes (DEGs). These DEGs were further analyzed by GO and KEGG enrichment analyses, PPI network and COX regression analysis. Transforming growth factor β1 (TGFβ1) was finally overlapped from the above analysis. Paired analysis and GSEA were carried out to understand the role of TGFβ1 in colon cancer. The intersection between the difference analysis and correlation analysis was conducted to learn the association between TGFβ1 and TICs. Results: Our results showed that immune component in TME was negatively related with the stages of CC. GO and KEGG enrichment analysis revealed that 1110 DEGs obtained from difference analysis were mainly enriched in immune-related activities. The intersection analysis between PPI network and COX regression analysis indicated that TGFβ1 was significantly associated with the communication of genes in PPI network and the survival of CC patients. In addition, TGFβ1 was up-regulated in the tumor samples and significantly related with poor prognosis of CC patients. Further GSEA suggested that genes in TGFβ1 up-regulated group were enriched in immune-related activities and the function of TGFβ1 might depend on the communications with TICs, including T cells CD4 naïve and T cells regulatory. Conclusions: The expression of TGFβ1 might be an indicator for tumor immune microenvironment of CC and serve as a prognostic factor. Drugs targeting TGFβ1 might be a potential immunotherapy for CC patients in the future.